Application of the al-Faqih Method in Improving the Ability to Read the Qur'an of Students of TPQ al-Hasaniyyah Rumbia Central Lampung | Penerapan Metode al-Faqih dalam Meningkatkan Kemampuan Membaca al-Qur'an Santri TPQ al-Hasaniyyah Rumbia Lampung Tengah - Erwanto, Nanang; Syaifullah, Muhammad; Honi, Muhammad Abdul (NAJAH BESTARI, 2024)
TPQ al Hasaniyyah Rumbia Central Lampung is one of the al Qur'an Education Institutions which is active in developing a young generation who loves the Qur'an. However, there are still many students who experience difficulties in reading the Koran clearly and fluently. This research aims to determine the effectiveness of using the al faqih method in improving the ability to read the Koran in students of TPQ al Hasaniyyah Rumbia Central Lampung. This research involved 10 students as participants, selected using purposive sampling technique. Data was collected through participant observation, in-depth interviews, and the data analysis used was thematic analysis. The results of this research are: (1) The implementation of learning at TPQ al Hasaniyyah Rumbia Central Lampung is active every day except friday nights, (2) implementation time is from 18.30 to 20.00 WIB, (3) the learning process begins with the opening prayer activity which is carried out by lining up on the TPQ page together, the main activity, the closing prayer activity, (4) al Faqih method, recently implemented at TPQ al Hasaniyyah Rumbia Central Lampung for approximately one year. However, according to the students, ustadz and ustadzah, guardians of the students, this method is considered quite effective in improving understanding of reading the al Qur'an and Arabic writing because the reading is easy to understand, uses tones, and is very enjoyable.